Analysis of proximate nutrient content in some selected fish of Bangladesh (Bangladesh Journal of Nutrition, 2018)
The study presents the content of moisture, fat, protein, ash and carbohydrate in some selected fish of Bangladesh. The study fishes include Ketchki fish {Coria soborna, Hamilton-Buchanan, 1822), Molafish (Amblypharyngodonmola, Hamilton-Buchanan, 1822), Poah fish {Panna microdon, Bleeker,1842), Tilapiafish (Oreochromismossambic, Peter, 1852), Silver carp fish (Hypohthalmichthys molitrix, Hamilton-Buchanan, 1822), Ruhi fish(Labeo rohita, Hamilton- Buchanan, 1822), Takhi fish {Channa punctatus, Bloch&Schneider, 1801), Pangasfish (Pangasius pangasius, Hamilton-Buchanan, 1822). The moisture content, in present study, was found to be in range of 71.9-80.73g%. Protein content was found in the range of 12.96-17.18g%. Ash content in the fish was found to be in range of 1.47-11.76g%. Fat content was found in the range of 1.4-11.76g%. Carbohydrate content in the fish was found to be in range of 1.04-3.5g%. Total calorie content in the fish was found to be in a range of 83.39-169.30Kcal/100g.Bangladesh J. Nutr. Vol. 28-31, December 2018, P: 19-23